International Economics Theory and Policy - Suranovic, Steve; Open Textbook Library (Open Textbook Library, 2012)
This text strives to reach a median between these two approaches. First, I believe that students need to learn the theory and models to understand how economists understand the world. I also think these ideas are accessible to most students if they are explained thoroughly. This text presents numerous models in some detail, not by employing advanced mathematics, but rather by walking students through a detailed description of how a model's assumptions influence its conclusions. Second, and perhaps more important, students must learn how the models connect with the real world. I believe that theory is done primarily to guide policy. We do positive economics to help answer the normative questions; for example, what should a country do about its trade policy or its exchange rate policy? The results from models give us insights that help us answer these questions. Thus this text strives to explain why each model is interesting by connecting its results to some aspect of a current policy issue. A prime example is found in Chapter 11 "Evaluating the Controversy between Free Trade and Protectionism" of this book, which addresses the age-old question of whether countries should choose free trade or some type of selected protection. The chapter demonstrates how the results of the various models presented throughout the text contribute to our understanding of this long-standing debate.
Preface -- Chapter 1: Introductory Trade Issues: History, Institutions, and Legal Framework -- Chapter 2: The Ricardian Theory of Comparative Advantage -- Chapter 3: The Pure Exchange Model of Trade -- Chapter 4: Factor Mobility and Income Redistribution -- Chapter 5: The Heckscher-Ohlin (Factor Proportions) Model -- Chapter 6: Economies of Scale and International Trade -- Chapter 7: Trade Policy Effects with Perfectly Competitive Markets -- Chapter 8: Domestic Policies and International Trade -- Chapter 9: Trade Policies with Market Imperfections and Distortions -- Chapter 10: Political Economy and International Trade -- Chapter 11: Evaluating the Controversy between Free Trade and Protectionism -- Chapter 12: Introductory Finance Issues: Current Patterns, Past History, and International Institutions -- Chapter 13: National Income and the Balance of Payments Accounts -- Chapter 14: The Whole Truth about Trade Imbalances -- Chapter 15: Foreign Exchange Markets and Rates of Return -- Chapter 16: Interest Rate Parity -- Chapter 17: Purchasing Power Parity -- Chapter 18: Interest Rate Determination -- Chapter 19: National Output Determination -- Chapter 20: The AA-DD Model -- Chapter 21: Policy Effects with Floating Exchange Rates -- Chapter 22: Fixed Exchange Rates -- Chapter 23: Policy Effects with Fixed Exchange Rates -- Chapter 24: Fixed versus Floating Exchange Rates
In English.
Description based on online resource
Keywords: Economics -- Textbooks; Political Science -- Textbooks